Disposition of debrisoquine and nortriptyline in Korean subjects in relation to CYP2D6 genotypes, and comparison with Caucasians - Dalén, P (Blackwell Science Inc, 2003)
AIMS: To study the influence of the CYP2D6*10 allele on the disposition of debrisoquine and nortriptyline. METHODS: The pharmacokinetics of debrisoquine and nortriptyline and their main metabolites were determined in ten Koreans with the CYP2D6*1/*1 (n = 5) and CYP2D6*1/*10 (n = 5) genotypes after single oral doses of 20 mg debrisoquine and 25 mg nortriptyline, respectively. The data were compared with previously published findings from 21 Caucasians with 0, one, two, three, four or 13 functional CYP2D6 genes. RESULTS: The AUC(0−8)of 4-hydroxydebrisoquine was significantly lower in Koreans with CYP2D6*1/*10 genotype compared with CYP2D6*1/*1[95% confidence interval (CI) for the ratio between means 1.17, 1.85]. No other genotype-related differences were found in the plasma kinetics of nortriptyline and debrisoquine, or their hydroxy metabolites. The AUC(nortriptyline)/AUC10-hydroxynortriptyline ratio did not differ between the *1/*1 and *1/*10 genotype groups (95% CI for the ratio of means 0.60, 1.26). Similarly, there was no difference between these genotypes with respect to the AUC(debrisoquine)/AUC4-hydroxydebrisoquine ratio (95% CI for the ratio of mean values 0.38, 1.46). Both Korean genotype groups had similar AUCs and parent compound/metabolite AUC ratios of debrisoquine and nortriptyline to Caucasians with two functional CYP2D6 genes. CONCLUSIONS: Heterozygosity for CYP2D6*10 decreases the CYP2D6-dependent elimination of nortriptyline and debrisoquine to only a limited degree. Further studies in subjects homozygous for CYP2D6*10 are required to elucidate fully the pharmacokinetic consequences of this CYP2D6 genotype in Orientals.